UPAYA MENINGKATKAN PEMBELAJARAN LOMPAT TINGGI DENGAN METODE BERMAIN DILINGKUNGAN PANTAI PADA SISWA KELAS VIII SMP NEGERI 1 WARUREJA KECAMATAN WARUREJA KEBUPATEN TEGAL TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to improve the high jump with a method of learning to play in coastalenvironments are students actively engaged in learning activities and encourage students to be more creative,foster self-confidence in learning. The method used in this research is Classroom Action Research (CAR). Theresearch was conducted at SMP Negeri 1 Warureja Tegal regency, the research subjects were students of classVIII B, amounting to 37 students.Data was collected through observation, tests and questionnaires. Forqualitative data analysis used observations of student activity sheets and questionnaires are used to determinestudents' responses, while quantitative data using the test, to determine student learning outcomes. ClassroomAction Research (CAR), there are two cycles with the same subject matter, where each cycle consists of fourphases: planning, action, observation and reflection. Results also showed an increase in student learning arepretty good views of the average student learning outcomes of each cycle. Average student learning outcomesfirst cycle of 7.80 and the second cycle of 8. This is reinforced by the students' response to the application of themethod to the beach to play in the presentation of cycle 1 and cycle 2 64.86% 92.43%. These results indicate anincrease in students' learning activities are quite high